NEGOSIASI EKSKLUSIVITAS: GAYA BAHASA HOST, KOMUNIKASI PERSUASIF, DAN MINAT BELI AUDIENCE PADA LIVE TIKTOK YSL BEAUTY OFFICIAL - Frida Solensia Tallo; Riswandi Riswandi (LPPM Universitas Putera Batam, 2026)
This study examines the negotiation of exclusivity in luxury brand communication through the host’s language style, persuasive communication, and the representation of audience purchase intention in YSL Beauty Official TikTok Live. Traditionally, luxury brands are associated with exclusivity, elegance, high prices, and limited accessibility. The presence of YSL Beauty on TikTok Live a platform commonly perceived as mass oriented and informal has generated public surprise and raised questions regarding the sustainability of luxury brand prestige in digital live commerce.This research employs a qualitative descriptive approach using content analysis. The data consist of verbal expressions delivered by the live host, visual presentation elements, and audience comments collected from selected YSL Beauty Official TikTok Live sessions. No interviews or surveys were conducted, as the study focuses on media content as a communicative text. Data were analyzed through thematic coding to identify patterns of language use, persuasive strategies, and indicators of purchase intention represented in audience interactions.The findings reveal that the host consistently adopts an elegant, soft, and polite language style that aligns with YSL’s luxury brand identity. Persuasive communication is performed through subtle and non-aggressive strategies, emphasizing product quality, sensory experience, brand credibility, and limited availability rather than price-driven promotion. Audience purchase intention is represented through comments expressing curiosity, admiration, product inquiries, and intentions to purchase.The study concludes that TikTok Live functions as a space of exclusivity negotiation, where YSL Beauty successfully reconstructs luxury values within a mass digital platform without diminishing its symbolic prestige.